The roles of Black women principals: evidence from two national surveys - Cheng, Albert; Coady, Emily; Maranto, Robert (Frontiers in Education, 2023)
While two-thirds of Black principals are female, the extant research on Black female principals is entirely qualitative. Using data from the 2017-2018 National Teacher and Principal Survey (n=7,165 with 453 Black female principals) and the 2011-2012 Schools and Staffing Survey (n=7,512, with 357 Black female principals), we quantitatively examine the career paths, reported influence, and reported time use of Black female principals compared to other principals. Black female principals are relatively less likely than Black male principals to have experience as athletic coaches, and less likely to have non-education management experience. Relative to non-Black female principals, Black female principals are less likely to have experience as curriculum directors. Relative to other principals, Black female principals generally report having comparable influence over their schools, while spending somewhat more time on parent interactions, suggestive of roles representing minority parents. We discuss implications and directions for future research.